Conceptualizing and researching governance in public and non-profit organizations - Gnan, Luca; Hinna, Alessandro; Monteduro, Fabio (Emerald, 2013)
The first volume of the series aims to give an outline of the state of the art and the most recent research being done on public and non profit governance at the international level (with particular emphasis in Europe). The focus of the volume is mainly on the organizational governance that still remains a neglected area of governance both in the public and in the non-profit sector. The volume includes two groups of chapters aimed at examining the recent trends and the future directions of the public and non-profit governance research. One group of chapters addresses broad issues of how to conceptualize and research 'governance' in public and non-profit organizations. The second group of chapters deals with recent trends of research on governance mechanisms through empirical studies, including contingency and behavioural studies on public and non-profit boards, studies on participative governance mechanisms such as stakeholder involvement and citizens participation and studies on governance codification.